SIMULATING THE EFFECT OF CLIMATE CHANGE ON WINTER WHEAT PRODUCTION AND WATER / NITROGEN USE EFFICIENCY IN IRAQ: CASE STUDY - & Shahadha, Masood (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2021)
The objective of this study was to investigate the capability of modifying the irrigation and nitrogen application rates as an adaptation to climate change, especially, increasing air temperature, using the Root Zone Water Quality Model (RZWQM2). Field experiments were conducted in the winter wheat season of 2015-2016 and 2019-2020 at the Rasheed County, south of Baghdad, Iraq. The effect of increasing air temperature on the water use efficiency, nitrogen use efficiency, and grain yield of wheat was assessed under different irrigation deficits and nitrogen application rates. Three levels of water depletion: 30, 50, and 70 of available water and four N application rates (0, 140, 200, and 260 kg N ha−1) were applied for winter wheat. Two temperature scenarios in the RZWQM2 were created for the study purpose. The first scenario was to add 2Co to the normal temperature, and the second scenario was to add 4Co to the normal temperature. Results showed that high irrigation levels presented better results than the low levels under projected temperature scenarios. However, all applied nitrogen rates presented similar results under projected temperature (2Co and 4Co scenarios). Therefore, modifying irrigation requirements is a workable adaption strategy to the increased temperature.